Evaluation of Attitudes of Students Studying at a Healthcare University Toward COVID-19 Vaccinations - Tapan, Birkan; Elbüken, Tuğçe; Özçelikçi, Büşra; Yildirim, Nurdan (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: In this study, it is aimed to evaluate the perspectives of individuals who will provide health services in the future, about the vaccine, which is created as a method of protection against the disease that affects the whole world. Methods: Demographic information, health information form and informed attitude scale towards COVID-19 vaccination were prepared by the researchers and used in the research conducted with 532 students of the University of Health in November-December 2021. Findings: Educational level in the group having an attitude score under 31 towards COVID-19 vaccination was found out to be meaningfully lower than the group having an attitude score above 31 towards COVID-19 vaccination(p < 0.05). The rate of diseases diagnosed by a doctor in the group having an attitude score under 31 towards COVID-19 vaccination was found out to be meaningfully higher than the group having an attitude score above 31 towards COVID-19 vaccination(p < 0.05). Results: According to the data obtained from our study, it was found out that attitude scores of students increased as their knowledge level increased. Even though healthcare professionals tend to accept vaccination, they should primarily be informed and educated on vaccination in an attempt to increase vaccination rates. It not only protects healthcare professionals that are exposed to high risk of infection but also reduces communication of the disease to their families. Their attitude towards vaccination also serves as a model for the vaccination of their patients and society.